Real-world effectiveness and safety of omalizumab in patients with uncontrolled severe allergic asthma from the Czech Republic - Kirchnerová, Olga Růžičková; Valena, Tomáš; Novosad, Jakub; Teřl, Milan; Czech eXpeRience Study Group (Postepy dermatologii i alergologii, 2019)
INTRODUCTION: This was a sub-group analysis of patients with uncontrolled persistent allergic asthma (AA) in the healthcare setting of the Czech Republic, from a global non-interventional, 2-year post-marketing, observational eXpeRience registry. AIM: To evaluate the real-life effectiveness and safety of omalizumab. MATERIAL AND METHODS: Patients with uncontrolled persistent AA (currently defined by the Global Initiative for Asthma (GINA) as uncontrolled severe AA) who started omalizumab treatment 15 weeks before inclusion in the registry were analysed for physicians' global evaluation of treatment effectiveness (GETE), asthma symptoms, corticosteroid use, exacerbation rate, asthma control, quality of life, healthcare utilisation and safety during a 24-month observation period. RESULTS: One hundred and fourteen patients from the Czech Republic were enrolled in the eXpeRience registry. A total of 88.9% of the patients were evaluated as responders to omalizumab according to the GETE assessment at week 16. From baseline to month 24: mean change in forced expiratory volume in 1 s (FEV1) was 137 ml and the daily dose of OCS decreased (11.6 mg to 6.4 mg prednisolone equivalent); the percentage of patients with no severe clinically significant exacerbations increased (29.5% to 95.1%); Asthma Control Test scores improved (12.4 to 17.3) and mean total number of days of asthma-related medical healthcare use decreased (6.8 days to 0.4 days). CONCLUSIONS: The results of this subgroup analysis support the evidence that add-on omalizumab therapy is effective and well tolerated for management of patients with uncontrolled persistent AA in the Czech Republic. Global evaluation of treatment effectiveness assessment is a reliable predictor of long-term response to omalizumab treatment.
Keywords: observational registry; allergic asthma; real-world study; omalizumab; asthma control; exacerbations